2013
DOI: 10.1111/jcpt.12095
|View full text |Cite
|
Sign up to set email alerts
|

Hyperchloraemic metabolic acidosis induced by the iron chelator deferasirox: a case report and review of the literature

Abstract: We describe herein a case of metabolic acidosis in the setting of treatment with the deferasirox. Our case and the literature indicate a potential risk of kidney toxicity on this agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
(26 reference statements)
3
10
1
Order By: Relevance
“…Also, during dose reduction but not total withdrawal, there was no resolution of renal tubular dysfunction. This finding was consistent with other case reports . Therefore this adverse effect of deferasirox may be idiosyncratic rather than dose‐dependent.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, during dose reduction but not total withdrawal, there was no resolution of renal tubular dysfunction. This finding was consistent with other case reports . Therefore this adverse effect of deferasirox may be idiosyncratic rather than dose‐dependent.…”
Section: Discussionsupporting
confidence: 93%
“…They all had metabolic acidosis and hypophosphataemia. Similarly, all the other case reports did not document complete FS. Most of these patients also had hypophosphataemia and/or normal anion gap metabolic acidosis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Acute kidney injury has been reported in the post-marketing surveillance of DFX [24,25]. Hyperchloraemic metabolic acidosis induced by DFX -that resolved after withdrawing -has also been reported previously [26]. In a multicentre randomized phase 3 trial, mild, dose dependent increases in serum creatinine were observed in 38% of patients receiving DFX at doses of 20-30 mg/kg/day.…”
Section: Discussionmentioning
confidence: 61%
“… 5. Deferasirox 139 143 increases hemodynamic iron removal, causes vacuolization of proximal tubular epithelial cells 142 , and elevates iron absorption in various organs. All could lead to acidosis.…”
Section: Drugs Causing Decreased Renal Acid Excretionmentioning
confidence: 99%